Адаптаційні стратегії економічного розвитку промислових підприємств в умовах кліматичної кризи та інноваційних трансформацій бізнес-моделей - Зеркаль, А.В. (Управління економікою: теорія та практика, 2025)
У статті розглядаються теоретичні засади формування адаптаційних стратегій економічного розвитку промислових підприємств в умовах загострення кліматичної кризи. Узагальнено світовий досвід інноваційної трансформації бізнес-моделей у промисловості та визначено механізми перетворення кліматичних ризиків на драйвери сталого розвитку. Проаналізовано ключові бар’єри та стимули трансформації бізнес-моделі в капіталомістких галузях, а також роль динамічних та абсорбційних організаційних здатностей у формуванні проактивних адаптаційних стратегій. Отримані результати можуть бути використані для планування стратегій декарбонізації та інтеграції принципів сталості у систему стратегічного управління підприємством. The article examines the theoretical foundations and practical mechanisms of adaptive strategies for the economic development of industrial enterprises under the intensifying climate crisis. The study systematizes international experience in transforming business models in capital-intensive industries and demonstrates how climate risks reshape the architecture of value creation. The research highlights that the adaptation of industrial enterprises is not limited to technological modernization but is achieved through the innovation-driven reconfiguration of business models, allowing firms to convert regulatory pressure and market shifts into sources of sustainable growth. The author identifies the key drivers and barriers of business model transformation, including decarbonization policies, new standards in global supply chains, investor expectations regarding environmental performance, as well as internal organizational constraints such as low absorptive capacity and inertia of corporate culture. Special attention is given to the role of dynamic and absorptive organizational capabilities, which determine the firm’s ability to integrate external knowledge, adopt sustainable practices, and form proactive strategies of adaptation. Based on the synthesis of global research, the article proposes a conceptual understanding of business model innovation as a core mechanism for transforming climate challenges into strategic opportunities. The results obtained can be applied by industrial enterprises in designing strategic programs of decarbonization, integrating sustainability principles into strategic management, and enhancing competitive resilience in global value chains.